The relationship between pure delamination modes i and II on the crack growth rate process in cracked lap shear specimen (CLS) of 5 harness satin composites - Shiino, M. Y. [UNESP] (2015)
Carbon fiber reinforced polymers (CFRP) structure can include dropping-off plies in order to comply with design requirements aiming at significant weight savings. However this type of discontinuity represents a potential source of delamination initiation and propagation which requires assessment of the mechanisms acting at the crack tip. This research investigates the influence of delamination modes I and II on the overall damage process observed in CLS specimen subjected to cyclic loads. The main contribution of this work focuses on the identification and physical interpretation of complex failure mechanisms in harness satin fabric. For this purpose a detailed fractographic analysis was carried out to qualitatively assess the surface fractures in these type of laminates. Results obtained for cyclic loaded CLS specimens were compared to analytical closed form solutions available in the literature. Results indicated that delamination front exhibited distinguishable delamination modes I and II propagating at constant mixed mode ratio (GI/GT).